(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Tuminico Formation is 1128 m thick in the Agua de la Peña creek and characterizes Late Carboniferous sedimentation linked to the Valle Fértil lineament (Fig. 1). For the characterization of the unit, 21 sedimentary facies (Table 1) were defined which correspond to diamictites (four facies), sandstones (eight facies), mudstones (five facies) and deposits with syn-sedimentary deformation (four facies). Diamictite facies corresponds to sandy massive diamictites (DSm facies), muddy massive diamictites (DFm), stratified diamictites (Ds) and thinly stratified diamictites (Dl). Sandstone facies include massive gravelly sandstones (SGm), coarse-grained, cross-bedded sandstones (Sge), medium-grained sandstones with hummocky/swaley cross-lamination (Smw), fine-grained, ripple cross-laminated sandstones containing dropstones (Sfrd), fine-grained, ripple cross-laminated sandstones (Sfr), fine-grained, horizontal-laminated sandstones (Sfh), muddy-sandstones showing heterolithic lamination (SFe) and rare cross-bedded conglomerates. Mudstone facies are composed of massive mudstones (Fm), shales (Fl), shales with dropstones (Fld), massive marls and massive muddy-marls (FMm) and rhythmites (R). Finally, rocks displaying intense syn-sedimentary deformation were divided in those dominated by folded sandstones (SXp), faulted sandstones (SXf), sandy lenses encapsulated in mudstones (SXl), and those exhibiting sedimentary boudinage (SXb). The Tuminico Formation, deposited in transitional to shallow marine environments, was divided in four stratigraphic intervals (Fig. 5 and 6). Section 1 is composed of 490 m of diamictites, pebbly-sandstones, and mudstones; all these rocks exhibit intense deformation (Fig. 9) and are interpreted as mass transport deposits (MTDs) deposited in subaqueous environments. The MTDs intervals are interstratified with non-deformed, thinly laminated diamictites and shales, which frequently contain dropstones. The alternation of highly deformed diamictites with undeformed shales indicates the recurrence of high-energy mass transport events within an overall low-energy environment fine-grained sedimentation (Fig. 9). Section 2 begins with a flooding surface that is overlain by a coarsening-and thickening-upward succession 185 m thick. The lower part of Section 2 displays a monotonous succession of shales and very fine-grained laminated sandstones, that pass upward to interbedded sandstones and mudstones. The uppermost part of the succession is comprised of cross-bedded coarse-grained sandstones and conglomerates. Section 2 is interpreted as being deposited in a prograding delta. Section 3 is 285 m thick and is divided in two intervals. The lower half consists of highly deformed MTDs deposits, that include all types of deformed diamictites, pebbly sandstones and mudstones. The upper half is composed of shales, fine-and medium-grained, laminated sandstones and some fine-grained, massive and cross-stratified conglomerates, forming a coarsening-upward cycle that is several meters thick. This upper part of the section 3 records the deposits of a progradational delta system with the common occurrence of syn-sedimentary deformation in both delta-front and platform deposits. In this stratigraphic level, fault-dominated deformation prevails, in the form of imbricate faults or slide blocks. This deformed interval is in some cases incised by fluvial channels that form the top of Section 3. Section 4 comprises 168 m of laminated and massive mudstones together with laminated very fine-and fine-grained sandstones. This stratigraphic interval, which corresponds to an important base-level rise, displays at least four transgressive-regressive cycles. The age of the studied deposits was determined by the presence of plant and palynological assemblages. Plant fossils collected in Section 3 (Fig. 5) correspond to the Nothorhacopteris/Botrychiopsis/ Ginkgophyllum (NBG) Biozone of Carboniferous age. Palynomorphs recovered from Sections 1, 2 and 3 correspond to the A subzones of the Raistrickia densa/ Convolutispora muriornata (DM) Biozone. The new paleontological data suggest a late Serpukhovian-early Bashkirian age for the Tuminico Formation. Regarding to the origin of the MTDs we suggest that tectonism could have triggered and/or amplified these events in late Carboniferous. This interpretation is supported by the recurrence of the MTDs intervals in the stratigraphic column, the high degree of deformation they display, and their considerable regional extent along Valle Fértil lineament of the MTDs. Finally, the significance of the unconformity that separates the Tuminico Formation (Late Carboniferous) and the overlying Talampaya Formation (Late Permian) is considered. In most of the Paganzo Basin the Talampaya Formation overlies the Early Permian Patquía Formation along a slight erosional unconformity. In the case of the Agua de La Peña creek exposures, not only the entire Patquía Formation is absent, but the underlying Pennsylvannian Tupe Formation is missing as well. Such a high level of erosion has been previously unrecognized in this area and may indicate also activity on the Valle Fértil lineament during the early stages of Permo-Triassic rift basin development in the region.